Evaluation of Task Shifting in Community-Based DOTS Program as an Effective Control Strategy for Tuberculosis - André P. Gabriel; Charles P. Mercado (The Scientific World Journal)
Tuberculosis (TB) remains to be the most prevalent and debilitating pulmonary (PTB) infection in the world today, affecting about one-third of the world's population. TB is an endemic disease in many developing countries, and efforts at eliminating the disease remain futile. While the course of the disease is indolent with years of latency, the reactivation of the disease can pose serious pulmonary and systemic infections that compromise multiple organ functions which lead to respiratory failure or end-organ damage. Despite attempts to control and eradicate the mycobacterium, the prevalence of the disease remains high due to increasing population rate, persistence of poverty and poor health care, treatment failure, increasing multidrug resistance as a consequence of treatment failure and poor compliance, and existence of comorbid conditions that compromise immune response. Limited government resources to screen and monitor disease progression of TB in third world countries hamper the eradication of the disease. In response, we have evaluated the efficiency and effectivity of a Community-Based Directly Observed Treatment, Short-Course (CB-DOTS), which is an equally effective alternative strategy to health center DOTS.